Management of Potential Drug Interaction in Community Pharmacies A Prescription Based Survey - Neetesh, Jain (International Journal of Pharmaceutical & Biological Archive, 2013)
Management of Potential Drug Interaction in Community Pharmacies A Prescription Based Survey